Screening of xylanase producer from soil - Lim, Ting Chin (2006)
The purpose of this study is to screen and to characterize the bacterial produce xylanase. The scopes are included screening, characterization of bacterial and xylanase and to study the effect of carbon and nitrogen source on the enzyme production ezyme. This research is start from the collect soil sample and screens the best xylanase producer from sample. After this, characterize xylanase producer in morphology. Besides this, need to characterize enzyme xylanase in the different temperature and pH ambient in term xylanase activity and protein activity. At the end, study the xylanase activity in various carbon and nitrogen source in volume fraction using Lowry method.The optimum xylanase activity.was obtained pH 7and 70oC is 13 U.And xylan is the best carbon source and organic nitrogen source is the best nitrogen source for production xylanase using this xylanase producer.